Chemical Characteristics, Antioxidant Activities, and Lead (Pb)-Chelating Ability of Powdered Drinks made from Coriander (Coriandrum sativum) Leaves Extract - Winarti, Sri; Sanjaya, Yushinta Aristina; Pertiwi, Cici Nagita (UPN Veteran Jatim, 2022)
Coriander is one of the natural antioxidant sources that can be used as chelating agent of heavy metals, such as lead (Pb) due to the presence of its phenolic compounds. However, the coriander has only been used as one of the spices on some dishes, and the other potential benefits have not been widely explored. Therefore, the processing of coriander leaves into a ready-to-drink (RTD) powdered beverage would be one of the ways to utilize the coriander. The objective of this study was to analyze the effect of drying temperature and maltodextrin concentration on product quality of powder drink. This study applied a complete randomized design of factorial pattern with two factors. The first factor was the drying temperature of 40oC, 50oC, and 60oC, while the second factor was the addition of maltodextrin as filler with the concentration of 5%, 10%, and 15%. The optimum treatment was observed at drying temperature of 40oC with maltodextrin concentration of 15%, yielding powder drink with water content of 4.19%; solubility of 89.92%; total phenol of 131.93 mg TAE/g; primary antioxidant activity of 47.05%; secondary antioxidant activity of 79.30%; and Pb reduction ability of 95.36%.